Is rituximab therapy a risk factor for development of melanoma? - Abdallah, Anas (My University, 2020)
In the literature, there are reports about dermoscopic and size changes of nevi in patients undergoing biologic therapy and chemotherapeutics. There has not been any established data for melanoma and Rituximab therapy. Sixteen patients, with 94 nevi were included in this study. Dermoscopic images of follow-up visits, which were performed at baseline, 3, 6, and 12 months after treatment, were evaluated. Suspicious lesions were excised. There was no increase in total nevus count. Although 61.7% of the 94 nevi have shown a stable duration without size changes, 26.5% had enlarged, and 11.7% had become smaller during our 1-year experience of dermoscopic monitoring. There was not any pattern transformation. Atypical dots and clods appeared in 17% of nevi. All of the excised nevi were comparable with Clark nevi, there was no clue for melanoma development. According to our results, we found that Rituximab therapy influences nevus morphology, but there is no evidence that this was linked to melanoma development.